Political power and social theory. Vol. 19 - Proenza-Coles, Christina; Davis, Diane E., 1953- (BIngley, UK : Emerald, 2008)
"Political Power and Social Theory" continues its longstanding run as a premier volume of comparative and historical social science. The volume focuses on a variety of questions relating to states, citizenship, and power, common themes examined with divergent analytical entry points and through deep knowledge of country cases as diverse as Russia, the United States, El Salvador, South Africa, and Israel. Whether examined with a focus on revolutions and political parties, or cities and their physical and social transformation, or through development of the concept of the 'familial state', which marries a preoccupation with lineage and micro-cultures to that of national-state institutions, these articles expand our theoretical and methodological imagination of how citizens become included or excluded in local and national structures of power.
Title from PDF t.p. (viewed 16 Jan., 2010).
Includes bibliographical references.
Description based on print version record.
Keywords: Political science; Power (Social sciences); Political sociology; Social sciences -- Philosophy; Social theory; Political science & theory; Political Science -- General